Arabic Learning Strategy in a Pesantren: Local Cultural Integration Perspective - Idhan, Mohamad; Hasnah, Sitti; Agustina, Putri Ayu Dia (Al-Hayat: Journal of Islamic Education, 2024)
Arabic language learning strategies have become widely discussed in recent decades. However, several existing studies still need to place learning strategies in the perspective of Local Cultural Integration. Departing from this condition, this study will elaborate on Arabic language learning strategies from the perspective of local cultural integration. Using a qualitative approach, with the type of field research. Data collection was carried out using interview techniques and direct observation. Data sources come from primary data such as interview results and secondary data such as several official government document reports. The research was conducted at the Nurul Iman Al-Khairaat Islamic Boarding School, Al-Ittihad DDI Islamic Boarding School, and Hikmatul Husna NW Islamic Boarding School. This article argues that learning strategies with the integration of Kaili local culture, including Mosipeli, Masiamasei, and Mosipopatora, are effective as Arabic language learning strategies in Islamic boarding school environments, as well as media for disseminating and strengthening identity, especially Islamic boarding school culture. The Arabic language learning methods of sorogan, bandongan, and wetonan integrate local culture into teaching strategies. This strategy is a counterweight to cultural hegemony and globalization in the Islamic boarding school environment. The limitation of this study lies in its scope which is limited to several specific Islamic boarding schools, thus, the generalization of the research results to all Islamic boarding schools in Indonesia may not be entirely accurate because each Islamic boarding school has different cultural characteristics and teaching systems. In terms of originality, the findings of this study provide an essential contribution to the world of Arabic language education by linking learning strategies with the integration of local culture, especially Kaili culture. This approach is rarely discussed in previous academic literature, which more often highlights conventional methods of teaching Arabic without connecting them to the local cultural context. This makes this study unique because it proposes a concept that integrates local culture as an essential element in Arabic language learning while countering the dominance of global culture, which often ignores traditional values.